DOES MILLENNIAL RATIONAL IN DECISION MAKING? THE IMPACT OF SELF-CONTROL AND E-MONEY ON COMPULSIVE BUYING: REFERENCE GROUP AS MODERATING VARIABLE - Rahman, Zainur; Santosa, Awan; Sumiyarsih, Sumiyarsih; Dwiarti, Rina; Huddin, Norlaile Salleh (Universitas Brawijaya, Indonesia, 2023)
The millennial generation is known as the sandwich generation, where they sometimes experience various problems in making decisions, including purchasing goods or services. These problems are essential to study regarding decision-making, especially in the digital era. There are various conveniences in conducting transactions, such as e-money. The millennial generation tends to compulsive buying for goods or services with various factors, both due to individual internal and external factors. This study aims to examine the effect of self-control and e-money on compulsive buying, which a reference group moderates. The sampling technique used is purposive sampling with a total of 249 respondents, where the sample criteria are the younger generation with e-money applications. The data analysis technique uses SEM-PLS to test the hypothesis. The results showed that self-control weakened compulsive buying due to the individual's ability to control himself in shopping. E-money usage has a positive effect on compulsive buying because of easier transactions. The novelty of this study used the reference group as a moderating variable, where the results of the reference group strengthen the influence of self-control on compulsive buying because individuals get positive information and suggestion from the group. Finally, the reference group can weaken the influence of e-money on compulsive buying. Although there is convenience in transacting, the presence of information from the group can prevent them from compulsive buying.